Influenza A(H3) whole genome analysis: searching causes for vaccine failure in 2011/2012 - Pechirra, Pedro (2017)
Background: The 2011/2012 season in Portugal, was characterized by an excess mortality and influenza vaccine failures. Predominant influenza A(H3) viruses with new antigenic properties were associated with potential host immune evasion. The aim of this study was to determine possible viral genetic causes that may be associated with cases of vaccine failure by performing a whole genome-based comparison of viruses detected in vaccinated (vacc) and unvaccinated (unvacc) individuals in 2011/2012 season. Methods: In 2011/12 season, 678 nasopharyngeal swabs from ILI cases were analyzed by the Portuguese NIC. Were detected 260 influenza A(H3) and 6 B/Yamagata viruses. For whole genome sequencing (WGS) 25 A(H3) positive samples, 20 from vacc and 5 from unvacc individuals, were selected. Each of the influenza genomic segments was submitted to standard or multiplex PCR amplification. WGS was performed on a MiSeq platform. Multiple alignments, phylogenetic and mutational analysis were performed using MEGA software 6.0. Results: Influenza A(H3) viruses clustered into different genetic clades, reflecting the clades circulating in Portugal, in2011/2012. 20 viruses belonged to clade 6 (reference strain A/Iowa/19/2010) and 5 viruses have clustered in the clade 3: 1 from clade 3A (A/Stockholm/18/2011), a second from clade 3B (A/England/259/2011) and 3 viruses from clade 3C (A/Victoria/361/2011). Viral genomes were highly similar at nucleotide level, ranging 98.2% – 100.0% of similarity. Matrix and nucleoprotein genomic segments were the most conserved, whereas the highest number of substitutions leading to amino acid changes was observed in hemagglutinin and neuraminidase segments (comparisons performed against the vaccine strain A/Perth/16/2009). The deduced amino acid sequences of viral proteins did not reveal any particular feature assigned to the group of vacc or unvacc individuals. Conclusions: In all 8 genomic segments of studied viruses no particular amino acid substitution was found to be associated with the vacc or unvacc cases. The observed differences were associated with the genetic distances between the clades to which viruses belong rather than with vaccine failure. Still, WGS in influenza surveillance is a powerful tool for monitoring the overall evolution of viral genome and establishment of molecular markers for, disease severity and drug resistance. This study points that a full evaluation of influenza vaccine failures should integrate not only data on virus characteristics, but also on host genetic polymorphisms related to immunity and serosurveys in order to better evaluate interindividual variation in influenza vaccine-induced immune responses.